Article RETRACTED due to manipulation by the authors Effect of Basic Water Confidence, Flexibility, and Technique on Freestyle Swimming Skill among Elementary School Pupils - Manill Kara Kauri; Yudik Prasetyo; Cerika Rismayanthi; Asmuddin Asmuddin; Abdul Saman; Muhammad Nazim Razali; Aida Mustapha; Syed Kamaruzaman Syed Ali; Hutkemri Hutkemri; Panggung Sutapa; Deni Hardianto; Rizqie Auliana; et al. (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The purpose of this study to examines the effect of differences between intervention programs using basic water confidence, flexibility, and freestyle swimming techniques on freestyle swimming skills. A quasi-experimental research design was adopted. There were three groups in this study, namely two experimental groups and one control group. The number of participants in the three groups was 90 people where they were carried out pre-test and post-test on freestyle swimming skills. The data analysis used is inferential testing, Covariance Analysis (ANCOVA), Assumption of Homogeneity of Variance, Data Normality Test and Statistical Assumption Test (T-test paired samples). Results. From the pre-test and post-test scores, ANCOVA results show that the effect of basic water confidence, flexibility, and freestyle swimming technique is significant on freestyle swimming skills at a good level. Next, a paired sample t-test was conducted, the results of the flexibility exercise with the highest score, while the group with the basic water confidence exercise got a pretty good score, although not as high as the score achieved by the group that did the flexibility exercise. While the scores with practice with freestyle swimming techniques did not show a significant effect on freestyle swimming skills. Conclusions. Thus, the findings prove that training with water-based confidence and flexibility has been shown to improve freestyle swimming skills in elementary school students. However, when this form of exercise must be applied in the appropriate order, starting with flexibility exercises, basic water confidence, and freestyle swimming technique to achieve freestyle swimming skills in elementary school students.